Competence Anti Impact Of Critical Factors Of BPR : A Case Study Of The Libyan Sector - Mohamed Maki, Ahmed (Universiti Sains Malaysia, 2003)
In the increasingly competitive environment of the 21st century, changes are inevitable in any organization that wishes to survive; the key to success is how to manage that change. Business Process Reengineering (BPR) has become a vital key for this change. This dissertation presents a holistic review of the literature related to BPR. Its review of the literature relating to the BPR critical factors that cause success and failure for BPR implementation, classifies these factors into subgroups, and identifies key factors of success and failure.